2015
DOI: 10.1186/s12864-015-1999-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial transcriptome reorganization in thermal adaptive evolution

Abstract: BackgroundEvolution optimizes a living system at both the genome and transcriptome levels. Few studies have investigated transcriptome evolution, whereas many studies have explored genome evolution in experimentally evolved cells. However, a comprehensive understanding of evolutionary mechanisms requires knowledge of how evolution shapes gene expression. Here, we analyzed Escherichia coli strains acquired during long-term thermal adaptive evolution.ResultsEvolved and ancestor Escherichia coli cells were expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…1B). In addition, the genes located in the deleted regions were clustered according to the gene categories (summarized in Supplementary Table S1) and subjected to enrichment analysis to identify the significant loss of gene function in each strain (reduced genomes), as previously reported 29 , 30 , 31 . Bimodal tests revealed that the deleted genomic sequences were most significantly enriched in the gene category of phage/IS-related function (h) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1B). In addition, the genes located in the deleted regions were clustered according to the gene categories (summarized in Supplementary Table S1) and subjected to enrichment analysis to identify the significant loss of gene function in each strain (reduced genomes), as previously reported 29 , 30 , 31 . Bimodal tests revealed that the deleted genomic sequences were most significantly enriched in the gene category of phage/IS-related function (h) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Such a global effect of bacterial growth has been demonstrated by the correlation between transcriptome and growth fitness 27 , 28 in both adaptation 29 , 30 and evolution 31 . However, studies constructing reduced genomes have reported diverse evidence regarding growth.…”
Section: Introductionmentioning
confidence: 99%
“…The biological replicates were averaged to generate a representative gene expression value under each condition. The growth data sets of the exponentially growing E. coli cells were adopted from the associated papers ( 30 , 40 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our studies critically consider the correlation between cell growth rate and the transcriptome. Thus, the following experimental procedures, which were excluded from the Materials and Methods of the original papers [4] , [5] , [6] , were performed. The details described here can be used to reproduce our deposited transcriptome data sets and the corresponding analytical results.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The genetic backgrounds of the Escherichia coli ( E. coli ) strains used for the transcriptome analyses are in previous reports [4] , [5] , [6] . An overview of these strains is shown in the Specifications table in the Data in Brief .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%